2021
DOI: 10.56983/jlta.v1i2.217
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Ability in Using Subject Verb Agreement in Writing an Essay

Abstract: This study aimed at finding out how the students' skills in using subject-verb agreement in writing essays. This research method is descriptive quantitative method. The research data was collected through the writing test as an instrument. The sample of this research was the fifth-semester students of English Education at the Alauddin State Islamic University of Makassar. The sample was taken by using simple random sampling. Based on the analysis and discussion about this research, the researcher concluded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Furthermore, from the findings it can be seen that the students in general perceive that Subject-Verb Agreement is very important (aver.score 83.6) and students in general perceive that their competence in S-V agreement is good (ave.score 66). This statement is in accordance with the findings of study from Dinilah, stating that the students' ability in using subject-verb agreement was categorized into a very good level [22]. Next this is the findings of sentence varieties: they stated that it is very important (ave.score 82.5) and they claimed that in general they perceive that their competence in Sentence Varieties is good (ave.score 69.1).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, from the findings it can be seen that the students in general perceive that Subject-Verb Agreement is very important (aver.score 83.6) and students in general perceive that their competence in S-V agreement is good (ave.score 66). This statement is in accordance with the findings of study from Dinilah, stating that the students' ability in using subject-verb agreement was categorized into a very good level [22]. Next this is the findings of sentence varieties: they stated that it is very important (ave.score 82.5) and they claimed that in general they perceive that their competence in Sentence Varieties is good (ave.score 69.1).…”
Section: Discussionsupporting
confidence: 87%
“…One important aspect of grammar in writing is the Subject-Verb Agreement. To write good and grammatically correct sentences, students need to pay attention to the relationship between the subject and the verb (subject-verb agreement) in each sentence (Dinillah et al, 2021). Therefore, it can be concluded that mastering the subject-verb agreement is very essential for students as a basis for writing so that they can produce precise and good writing.…”
Section: Introductionmentioning
confidence: 99%